PENGARUH UMUR KECAMBAH DAN DOSIS PUPUK UREA TERHADAP PERTUMBUHAN BIBIT KAKAO - Erida Nurahmi; Yuswar Yunus; Yennita Yennita (Program Studi Agroteknologi, Fakultas Pertanian, Universitas Syiah Kuala, 2013)
Cacao is an important plantation plant in Indonesia for its contribution to our income. The productivity of this plant still have a chance to be increased, with the improvement in culture technique. One limited information concerning the cacao cultivation technique is seedling ages and urea dosages when transplanting. The purposes of this research were to find out the effect of seedling ages, urea dosages, and interaction between them on cacao seedling growth at nursery. Research was conducted at Experimental Station of Agriculture Faculty, University of Syiah Kuala. Units of treatment were arranged according to Factorial Randomized Complete Block Design with 4 replicates, followed by Honestly Significant Different Test at the level of 5%. Seeds were extracted from 1/3 of cacao mature fruits at the center of the pod and germinated in germination box filled with sand and covered by wet towel. Growing medium used was top soil:manure:sand=2:1:1 (by volume). Variables observed were seedling height, stem diameter, leaf number and area, primary root length, and wet and dry mass of seedling at 45, 60 75 and 90 days after transplanting. Results showed that there were significant interactions between treatments on all variables observed. The best combination was age of 10 days of seedling and dosage of 2 g urea per polybag.